2013
DOI: 10.1530/eje-12-0808
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of glucocorticoid receptor polymorphisms in relation to metabolic parameters in Addison's disease

Abstract: Background: Uncertainty exists whether glucocorticoid receptor (GCR) polymorphisms play a role in steroid-related side effects in Addison's disease (AD) patients on hydrocortisone. The polymorphisms Bcll and N363S appear to increase sensitivity to cortisol, while the ER22/23EK polymorphism has been associated with resistance to cortisol. Method: One hundred and forty seven AD patients, and gender, and ethnicity-matched controls were recruited in South Africa. Three polymorphisms in the GCR were studied, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…ER22/23EK is a polymorphism located on exon 2 and comprises of two nucleotide substitutions, of which only the second polymorphism results in the substitution of an amino acid which has an impact on the tertiary structure of GR, thereby affecting activation of transcription. The presence of ER22/23EK polymorphism is reported to decrease glucocorticoid sensitivity [103], increase muscle mass [104], BMI, triglyceride levels and hs-CRP [103] and increased the risk of depression.…”
Section: Glucocorticoid Receptor Polymorphismmentioning
confidence: 99%
“…ER22/23EK is a polymorphism located on exon 2 and comprises of two nucleotide substitutions, of which only the second polymorphism results in the substitution of an amino acid which has an impact on the tertiary structure of GR, thereby affecting activation of transcription. The presence of ER22/23EK polymorphism is reported to decrease glucocorticoid sensitivity [103], increase muscle mass [104], BMI, triglyceride levels and hs-CRP [103] and increased the risk of depression.…”
Section: Glucocorticoid Receptor Polymorphismmentioning
confidence: 99%
“…Ross et al previously studied the effects of the above polymorphisms in patients with AD and found that the ER22/23EK polymorphism was counter-intuitively associated with an increased BMI, but lower LDL-cholesterol. The mean hydrocortisone dose was higher in patients with either the ER22/23EK or N363S polymorphism [4]. We now report the results of our analysis of the 9β polymorphism in the same cohort.…”
Section: Introductionmentioning
confidence: 59%
“…The ER22/23EK polymorphism was somewhat unexpectedly associated with higher BMI, lower LDLC and higher doses of hydrocortisone. Similarly AD patients with the N363S polymorphism also received higher doses of hydrocortisone [4]. Several other studies of GCR polymorphisms have also either failed to show significant metabolic associations or have shown metabolic alterations that are difficult to reconcile with the reported changes in glucocorticoid sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the study did not address effects of extra doses in other types of physical stress, i.e., repeated doses and extensive or prolonged physical activity. Moreover, individual HC requirement is influenced by HC absorption, metabolism and individual sensitivity to glucocorticoids (17,18), and hence proper stress doses would have to be individualized in a clinical setting. Thus, true effects of stress dosing may be concealed by large individual variation and statistical type II error.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%